Culture-Based Teaching: Integrating Indonesian Culture in English Language Teaching (ELT) - Nur Fitria, Tira (Universitas Kristen Cipta Wacana, 2025)
This research describes the integration of Indonesian culture into English Language Teaching (ELT). This research is library research. The analysis shows that integrating Indonesian culture into English learning is crucial supported by the nation's commitment to